Keberlanjutan Kurikulum Berbasis Kompetensi Dalam Meningkatkan Mutu Pendidikan Akuntansi Pada 5 (Lima) Perguruan Tinggi Swasta Di Surabaya - Anita Permatasari; Martinus Sony Erstiawan (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2013)
Curriculum as a high education implementation tool that has to be dynamic, therefore periodically it is required to be evaluated and enhanced in accordance with the development of knowledge and technology. The current issue is how the continuance of competency-based curriculum increases the quality of accounting education at five private universities in Surabaya. Research question related to graduating competency standard, cuticulum structure, learning materials, syllabus and the learning implementation plan in standing by the learning activity, the role of lecturer in enacting SCL-centered learning method, appraisal of learning result and learning process evaluation. The objective of this study is to examine and to evaluate development process and the continuance of competency-based curriculum implementation to accounting high education. The used research type is qualitative description research with Research and Development (R&D).In the education research there are research of knowledge aspect and education practices, knowledge and curriculum practices, learning practices, knowledge with guidance and counseling practices, and knowledge with education management practices. If they. Are carried out in the accounting education research in order to describe a process of education activity based on what occurs in the field as further study material to find out the shortage and the weakness of accounting education program so that those can be required to improve the curriculum and to adapt to the world of work today. The conclusion which is gained in this research states that the curriculum of bachelor degree’s accounting study program at faculty of economics Wijaya Putra University, faculty of economics Darma Cendika Catholic university and Faculty Of Economics Merdeka University, implementation of KBK’s continuance requires much more gradually and continually improvement. While Faculty Of Business Widya Mandala Catholic University And Indonesia School Of Economics (STIESIA) have applied competency-based curriculum eventhough there is still much that needs to be improved gradually and continually so as to produce the quality of the college itself and the quality of graduates.